Enrichment Mechanism of the Upper Carboniferous-Lower Permian Transitional Shale in the East Margin of the Ordos Basin, China: Evidence from Geochemical Proxies - Zhifu Wei; Yongli Wang; Gen Wang; Ting Zhang; Wei He; Xueyun Ma; Xiaoli Yu (Geofluids)
The organic-rich shale of the Upper Carboniferous-Lower Permian transition period in the eastern margin of the Ordos Basin, China, was formed in a marine-continental facies sedimentary environment. With a high content of total organic carbon (TOC) and a large cumulative thickness, it is considered a good source rock for shale gas development. The sedimentary environment of marine-continental transitional shale is obviously different from that of marine shale, which leads to different enrichment characteristics of organic matter. In this paper, shale samples were collected from XX# well of the Taiyuan and Shanxi Formations across the Upper Carboniferous-Lower Permian, which is typical marine-continental transitional shale. The TOC, major elements, and trace elements were measured, and the formation and preservation conditions were investigated using multiple geochemical proxies, including paleoclimate, redox parameters, paleoproductivity, and controls on the accumulation of organic matter. The TOC of Shanxi Formation is higher than that of Taiyuan Formation. In the Taiyuan Formation, TOC is positively related to the redox index (V, U, and V/Cr), indicating that the dysoxic bottom water environment is the key factor controlling organic matter accumulation. For Shanxi Formation, there is a positive correlation between TOC and paleoclimate, which indicates that the enrichment of organic matter is affected by warm and humid paleoclimate and oxic environment. In addition, the paleoproductivity is lower with a positive correlation with TOC for the marine-continental transitional organic-rich shale, suggesting that it was inferior to the gathering of organic matter.